Lethal factor antibodies contribute to lethal toxin neutralization in recipients of anthrax vaccine precipitated. Issue 26 (8th June 2017) - Dumas, Eric K.; Garman, Lori; Cuthbertson, Hannah; Charlton, Sue; Hallis, Bassam; Engler, Renata J.M.; Choudhari, Shyamal; Picking, William D.; James, Judith A.; Farris, A. Darise
Highlights: AVP and matched AVA recipients make similar IgG responses to PA. AVP recipients have higher ED50 LT neutralization responses. LF IgG makes additive contribution to LT neutralization in AVP recipients. LF antibodies affinity purified from AVP recipients bind Domain 1 and neutralize LT. Gender influences humoral immunity to AVP and AVA. Abstract: A major difference between two currently licensed anthrax vaccines is presence (United Kingdom Anthrax Vaccine Precipitated, AVP) or absence (United States Anthrax Vaccine Adsorbed, AVA) of quantifiable amounts of the Lethal Toxin (LT) component Lethal Factor (LF). The primary immunogen in both vaccine formulations is Protective Antigen (PA), and LT-neutralizing antibodies directed to PA are an accepted correlate of vaccine efficacy; however, vaccination studies in animal models have demonstrated that LF antibodies can be protective. In this report we compared humoral immune responses in cohorts of AVP (n = 39) and AVA recipients (n = 78) matched 1:2 for number of vaccinations and time post-vaccination, and evaluated whether the LF response contributes to LT neutralization in human recipients of AVP. PA response rates (≥95%) and PA IgG concentrations were similar in both groups; however, AVP recipients exhibited higher LT neutralization ED50 values (AVP: 1464.0 ± 214.7, AVA: 544.9 ± 83.2, p < 0.0001) and had higher rates of LF IgG positivity (95%) compared to matched AVA vaccinees (1%). Multiple regression analysis revealed that LF IgG makes an independent and additive contribution to the LT neutralization response in the AVP group. Affinity purified LF antibodies from two independent AVP recipients neutralized LT and bound to LF Domain 1, confirming contribution of LF antibodies to LT neutralization. This study documents the benefit of including an LF component to PA-based anthrax vaccines.